PENERAPAN MODEL PEMBELAJARAN ARTIKULASI BERBANTUAN KAHOOT DALAM MENINGKATKAN KETERAMPILAN MENYIMAK CERITA RAKYAT (HIKAYAT) KELAS X - Devi Puspita Ayu; Khaerunnisa (STKIP Muhammadiyah Bogor, 2021)
The background of the research is the low folklore listening skills and the lack of learning models and media applied to class X. It has impact to the students’ scores for under the KKM. This research was conducted during the Covid-19 (coronavirus disease) pandemic which implements distance learning (online) in class X MIPA 2 SMA Nusantara Plus, with total 26 students of the 2020/2021 school year. The research method used in this research is Classroom Action Research (CAR). Learning activities using this articulation model make the learning process easier to listen folklores. Kahoot media known as an attractive and more efficient evaluation media. This research was conducted in two cycles, in each cycle there were two meetings. The results of this study indicate an increase in the ability to listen to saga stories. This can be seen from the results of the pre-cycle average score of 55, cycle I increased to 70 but did not meet the KKM, followed by cycle II with an average value of 86. Thus it can be concluded that the use of Kahoot in articulation learning model can improve folklore listening skills of class X SMA Nusantara Plus. Keywords: articulation learning model, Kahoot, listening skills, folklores